2017
DOI: 10.1021/acschemneuro.6b00447
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of a Novel α2/α3-Subtype Selective GABAA Receptor Positive Allosteric Modulator

Abstract: Pain remains a challenging clinical condition and spinal GABAA receptors are crucial modulators of pain processing. α2/α3-subtype GABAA receptors mediate the analgesic actions of benzodiazepines. Positive allosteric modulators (PAMs) at α2/α3-subtype GABAA receptors may have analgesic potential. Here we report a new selective α2/α3-subtype GABAA receptor PAM in in vitro and in vivo pain assays. KRM-II-81 demonstrated similar efficacy at α1/α2/α3 GABAA receptors and negligible efficacy at α4/α5/α6 GABAA recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…GL-II-75 exhibited high potentiation at all four subunits, suggesting shared electrophysiological properties with the non-selective PAM DZP. Indeed, at the same concentration (100 nM), DZP induces a slightly more robust potentiation at α1, α2, α3, and α5-containing GABAA receptors of the magnitude > 200% [37]. The profiles at 100 nM were confirmed at 1 µM concentration, with strong α5-PAM effects ( t test comparison to 100%; t > 4.67; p < 0.009) and lower potentiation at α1, α2, and α3 for GL-II-73 and GL-II-74 ( t > 3.17; p < 0.03).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GL-II-75 exhibited high potentiation at all four subunits, suggesting shared electrophysiological properties with the non-selective PAM DZP. Indeed, at the same concentration (100 nM), DZP induces a slightly more robust potentiation at α1, α2, α3, and α5-containing GABAA receptors of the magnitude > 200% [37]. The profiles at 100 nM were confirmed at 1 µM concentration, with strong α5-PAM effects ( t test comparison to 100%; t > 4.67; p < 0.009) and lower potentiation at α1, α2, and α3 for GL-II-73 and GL-II-74 ( t > 3.17; p < 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Binding and electrophysiological studies indicated that GL-II-73 and GL-II-74 acted as PAMs with priority affinity and efficacy at α5-GABAA-Rs, whereas GL-II-75 potentiated GABA-gated chloride current to a greater extent at α1-, α2-, and α3-GABAA-Rs compared to α5-GABAA-R, suggesting properties closer to DZP [37], although with much lower overall affinity than DZP. The lack of potentiation at GABAA-Rs containing the α4, α6, or δ subunits supports the notion that all ligands bind to the DZP-specific BZ-sensitive site of GABAA-Rs [12].…”
Section: Discussionmentioning
confidence: 99%
“…At 100nM, GL-II-74 and GL-II-75 exhibit substantial allosteric modulation at α5-GABAA-Rs, while GL-II-73 and GL-II-76 exhibited lower, but still significant, potentiation (t-test comparison to 100%; t>2.9; p<0.04). At this low concentration, all compounds also potentiate α1, α2 and α3-GABAA-Rs (t>2.9; p<0.04), GL-II-75 already exhibiting high potentiation at this subunits, suggesting shared electrophysiological properties with the referent non-selective PAM DZP (48,49). The profiles at 100nM were confirmed at 1µM concentration, with strong α5-PAM effects (t-test comparison to 100%; t>4.67; p<0.009), and still significant potentiation at α1,α2 and α3 (t>3.17; p<0.03).…”
Section: Novel Ibzd Amide Ligands Potentiate α-Containing Gabaa-rsmentioning
confidence: 89%
“…This novel finding underlines the importance of better understanding the differences in allosteric modulation of GABA A receptors expressing α3 compared to other α subunits. For example, nonhypnotic drugs targeting the α2 and α3 subunits have been studied for their anxiolytic and analgesic effects . However, creating ligands that distinguish these two subunits remains difficult, as shown when an “α3‐specific” PAM (SB‐205384) was found to potentiate α6‐containing GABA A receptors even more strongly than α3 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, nonhypnotic drugs targeting the α2 and α3 subunits have been studied for their anxiolytic and analgesic effects. 41,45 However, creating ligands that distinguish these two subunits remains difficult, as shown when an "α3-specific" PAM (SB-205384) was found to potentiate α6-containing GABA A receptors even more strongly than α3. 46 Another way to distinguish different GABA A receptor subtypes is through the γ subunit.…”
Section: Discussionmentioning
confidence: 99%